The Effect of Workplace Negative Gossip on Employee Proactive Behavior in China: The Moderating Role of Traditionality - Wu, Xiangfan (Journal of business ethics, 2018)
In this study, we examined the relationship between workplace negative gossip, as perceived by the targets, and proactive behavior by focusing on the mediating role of the target’s emotional exhaustion and the moderating role of the target’s traditionality. Our results from dyadic data on 234 supervisor–subordinate relationships in China revealed that (1) workplace negative gossip was negatively related to proactive behavior; (2) emotional exhaustion mediated this relationship; and (3) traditionality strengthened both the relationship between workplace negative gossip and emotional exhaustion and the indirect effect of workplace negative gossip on proactive behavior via emotional exhaustion. Our findings have a number of theoretical and practical implications for the research on mistreatment and proactive behavior.